PENGABDIAN KEPADA MASYARAKAT MELALUI PELATIHAN DIGITAL PADA PERANGKAT DESA SINGAPADU KALER SUKAWATI GIANYAR - I Made Darmada; I Komang Sukendra; I Made Surat; I Nyoman Bagus Suweta Nugraha (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2024)
Digitalization is the use of digital data technology in order to create or improve processes used to improve business, results and create a digital culture. There is a need for digitalization of village administration in the services provided by the village government. This activity aims to provide digital understanding to Singapadu Kalee village officials regarding the importance of digital transformation at the village level. With the increasing development of technology and information, villages can take advantage of the opportunities offered by the digital revolution to improve the welfare of the people of Singapadu Kaler village. The method used is training designed in the form of practice in using village information systems. The location for the training was held in the meeting room of Silakarang Vocational School, Singapadu Kaler village. The training participants consisted of 20 village and community officials. Training is carried out in 3 stages, namely preparation, implementation and evaluation. The results of the training show that through the village data digitization system it can facilitate communication between the government and the residents of Singapadu Kaler village. Through digital training, village officials can improve the skills and knowledge of village officials in using information systems. To understand various aspects of digital technology, including the application of information systems, digital data management, online marketing, and technology-based public services.